(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
This article examines the function of religion in Nigerian Society, emphasizing its contribution to social cohesion, moral guidance, and communal identity. Religion enhances societal welfare, ethical governance, and communal assistance while exerting social, educational, and humanistic impacts. Nonetheless, the paper underscores the detriments linked to religion, such as sectarian conflicts, intolerance, as well as politicization, which exacerbate political and ethnic divisions. It reveals the factors contributing to Nigeria’s religious landscape’s intricacy, including religious extremism, prejudice, and economic challenges arising from religious obligations. The research advocates for more interfaith communication to leverage the beneficial aspects of religion while mitigating its adverse effects.